EVALUASI DRUG RELATED PROBLEMS PENGGUNAAN OBAT ANTIDIABETES PADA PASIEN DIABETES MELITUS TIPE 2 DI INSTALASI FARMASI RAWAT INAP RUMAH SAKIT TK.III DR. R. SOEHARSONO - Nazhipah Isnani; Muliyani Muliyani; Muhammad Zaini; Putri Sheila Wardhani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Diabetes mellitus is a disease characterized by hyperglycemia and disturbances of carbohydrate, fat and protein metabolism associated with absolute or relative deficiency of insulin action and/or secretion. The purpose of this study was to determine the characteristics of type 2 DM patients and whether there were DRPs (Drug Related Problems) using antidiabetic drugs in patients with Type 2 Diabetes Mellitus at the Inpatient Pharmacy Installation of Tk.III Hospital Dr. R. Soeharsono period 2019-2020. This research is a non-experimental research with a descriptive research design with a retrospective approach. The sampling technique used was total sampling with a sample of 42 patients taken from the medical records of type 2 DM patients who received antidiabetic drugs at the Inpatient Pharmacy Installation of Tk.III Hospital Dr. R. Soeharsono Banjarmasin. From the results of this study, type 2 diabetes was mostly experienced by women, 25 patients (60%) with an age range of 41-60 years (62%), with the most diabetes complications being hypertension (59.5%). The results of the study of 42 patients studied, there were 22 patients (52.3%) who experienced DRPs by category in a row, namely drug interactions (33.3%), drugs without indications (14%), indications without drugs (4 ,7%), wrong drug (2.4%), under dos